2017
DOI: 10.1590/1981-22562017020.160090
|View full text |Cite
|
Sign up to set email alerts
|

Lack of accessibility in public transport and inadequacy of sidewalks: effects on the social participation of elderly persons with functional limitations

Abstract: Objective: To analyze the association between the decline in the mobility of community dwelling elderly persons in São Paulo, Brazil and their capacity to use public transportation, and its impact on their quality of life and social participation. Method: A cross-sectional study was conducted of 32 community dwelling elderly persons, of both genders (59% female), with an average age of 75.5 years (±9.2). The participants were evaluated by functional mobility, risk of falls, fear of falls and independence in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…The statistical model of our study revealed three predictive variables that influence social participation: functional mobility was the variable with the greatest association, followed by cognitive function and the muscle strength of lower limbs. Santos et al 20 found evidence of a result like ours. They analyzed the impact of functional mobility on the quality of life and social participation of older adults.…”
Section: Discussionsupporting
confidence: 77%
“…The statistical model of our study revealed three predictive variables that influence social participation: functional mobility was the variable with the greatest association, followed by cognitive function and the muscle strength of lower limbs. Santos et al 20 found evidence of a result like ours. They analyzed the impact of functional mobility on the quality of life and social participation of older adults.…”
Section: Discussionsupporting
confidence: 77%
“…A further 16% needed to walk for more than five minutes while 34% had to take a paratransit (auto rickshaw or taxi) to reach a bus stop or the Metrobus. Santos et al (2017) pointed out that irregular sidewalks, inaccessible public transport and other characteristics of the built environment can create barriers to the mobility of elderly people thus reduce their use of public transport.…”
Section: Resultsmentioning
confidence: 99%
“…A lei n. 12.587, de 3 de janeiro de 2012, que institui as diretrizes da Política Nacional de Mobilidade Urbana (Brasil, 2012), explicita a prioridade aos modos de transporte não motorizados, não fornecendo, no entanto, diretrizes que a garantam e viabilizem. Enquanto não houver uma política pública que trate com responsabilidade e eficiência as calçadas das cidades, livrando-as das irregularidades cometidas pela parceria público-privada com que são regidas atualmente, os idosos continuarão a ser as maiores vítimas do acidente de trânsito mais usual: a queda nas calçadas (Santos et al, 2017). Na cidade de São Paulo, por exemplo, proprietários de lotes são responsáveis pela construção, reforma e manutenção de calçadas contíguas, cabendo, ao poder público, fornecer as diretrizes de como fazê-lo e fiscalizar o seu cumprimento (São Paulo (Município), 2011).…”
Section: Análise E Discussãounclassified